READING THE TERM DALÂL IN THE QUR’AN - Prasetyo, Ahmad Baliyo Eko (Millah: Journal of Religious Studies, 2008)
Book Review: Book Title : Kesesatan dalam Perspektif Al-Qur’an Author : Aibdi Rahmat Publisher : Pustaka Pelajar, Yogyakarta Edition : I, March 2007 Content : viii + 228 pages